Delayed cystic fibrosis diagnosis due to presumed celiac disease-A case report from Syria - Yahia Ranjous; Abdulrahman Al Balkhi; Nazir Alahmad; Ali Asaad; Ayman Ali (BMC, 2023)
Abstract Background This case report describes a cystic fibrosis case after 7 years of a presumed diagnosis of celiac disease without confirming laboratory tests and biopsies. Both cystic fibrosis and celiac disease cause malnutrition, malabsorption, and failure to thrive. Also, the occurrence of cystic fibrosis in celiac disease patients is higher than in the normal population. Therefore, the differentiation between the two diseases might be challenging. This article highlights the reason for the confusion between cystic fibrosis and celiac disease and emphasizes the importance of not skipping the necessary investigations no matter how difficult it is to perform them. Case presentation This report details the case history of a patient presumed to have celiac disease for 7 years without confirming investigations. He developed multiple respiratory infections and weight loss throughout the 7 years but was only diagnosed with cystic fibrosis after hospitalization for gradual abdominal distension and productive cough. Chest CT showed atelectasis in the right upper lobe, tree-in-bud sign on both sides, and right periumbilical mass with several enlargements in the mediastinal nodes. Ascites paracentesis revealed a high SAAG gradient and low-protein fluid. The sweat chloride test resulted in a chloride level of 90 mEq/L, which confirmed the cystic fibrosis diagnosis. Subsequent genetic testing revealed the rare G85E mutation. Conclusion This report highlights the potential for diagnostic confusion between cystic fibrosis and celiac disease. Also, it reminds physicians about the importance of taking a detailed medical history and performing the essential investigations no matter how difficult it is to do them. Finally, it emphasizes the need to verify the patient's previous medical history in case there is no official documentation of his case. This should be considered particularly in rural areas in low-income countries where the possibility of medical malpractice should not be forgotten.